2010
DOI: 10.1002/fuce.201000048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the A Cation Size Disorder on the Properties of an Iron Perovskite Series for Their Use as Cathodes for SOFCs

Abstract: In order to develop a cathode that can be used in intermediate temperature solid oxide fuel cells, a family of iron perovskites with the general formula Ln0.5M0.5FeO3–δ (A = Ln1–xMx; Ln = La, Nd and/or Pr; M = Sr, Ca or/and Ba) with fixed divalent dopant concentration x to 0.5, mean A cation radius 〈rA〉 to 1.25 Å but with different A cation size disorder σ2(rA) has been prepared by the conventional solid state reaction. These compounds have been characterised by power X‐ray diffraction (XRD), high‐resolution s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…(Table 4) The electrical conductivities obtained are comparable with those previously reported for this type of perovskite material with high σ 2 (r A ) values [7,11]. However, in this study, a slight decrease in electrical conductivity was observed for the sample with G/N = 2 when a current of 100 mA was applied.…”
Section: Electrical Conductivity Studysupporting
confidence: 88%
See 2 more Smart Citations
“…(Table 4) The electrical conductivities obtained are comparable with those previously reported for this type of perovskite material with high σ 2 (r A ) values [7,11]. However, in this study, a slight decrease in electrical conductivity was observed for the sample with G/N = 2 when a current of 100 mA was applied.…”
Section: Electrical Conductivity Studysupporting
confidence: 88%
“…As have been studied for similar compositions with high values of σ 2 (r A ) [11,12], the Rp values are very sensitive to changes in applied currents. Figure 13 shows the typical Nyquist diagram of the impedance spectroscopy for Samples with G/N = 1 and 2 at 800°C at OCP and under a current of 50 and 100 mA.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, sintered pellets were cut in ~1 x 3 x 7 mm bars; the conductivity measurements were carried out with the standard dc four-point method on the rectangular sintered bars, from room temperature to 1000 ºC in air using a heating rate of 2 ºC•min -1 , using a power source controlled by PC using Lab Windows/CVI field point system. The measured conductivity values were corrected taking into account the porosity of the samples [21]. Thermal expansion measurements (TEC) for the contact layers, cathode and interconnect were carried out from room temperature to 1000 ºC in air with a heating rate of 5 ºC•min -1 by using a Unitherm Model 1161 dilatometer.…”
Section: Methodsmentioning
confidence: 99%
“…The proposed way to verify the goodness of a material as cathode can be carried out in addition to the conventional methods (such as the electrical measurements). [36][37] The oxygen redox process is affected by a lot of features; Adler, in his widely cited review, 38 summarizes the main ones.…”
Section: Permeation Measurementsmentioning
confidence: 99%